PEMBELAJARAN NILAI PADA ANAK SEBAGAI UPAYA PEMBENTUKAN KEPRIBADIAN - Mutmainah Mutmainah (MAJALAH ILMIAH PEMBELAJARAN, 2007)
Every parents wish to have children with moral and noble manner. These children will benefit not only their own life and their family but also their society. It is why every child should have moral and ethical education. Moral education is an educational process that is based on moral and ethics. In the attempt to teach moral and foster noble personality to children, parents need particular methods and strategy in nurturing their children. This method should be an agreement between the father and the mother so there will be consistency in the ruling, reward and punishment. Besides, parent’s exemplars are vital in children personality development.Parent’s effort in moral education and personality development consist of creating customary habits, dialog, exemplar, empathy, creating open environment and truthful behavior, inviting children to contemplation, giving respect to their children and put reward and punishment into practice. Reward and punishment are necessary to reinforce children behavior. Rewards are given to encourage children to maintain, repeat and improve good behavior while punishments are given to stop bad behavior. Some guidelines in applying rewards and punishments are: (1) do not punish when you are angry; (2) calm yourself; (3) do not punish to embarrass children; (4) Do not punish in front of people; (5) be consistent; (6) be proper; (7) punish at that time, do not delay. Parents are the accompaniment, the supervisor, the counselor and the role model for their children. Additionally, parents should be aware of the environment that may affect their children’s behavior.